CARMENES: Blue Planets Orbiting Red Dwarfs. Issue Volume 8:Issue S299(2013) (6th January 2014) - Quirrenbach, A.; Amado, P. J.; Caballero, J. A.; Mandel, H.; Mundt, R.; Reiners, A.; Ribas, I.; Carrasco, M. A. Sánchez; Seifert, W.; Azzaro, M.; Galadí, D.; ,
Abstract: CARMENES (C alarA lto high-R esolution search forM dwarfs withE xo-earths withN ear-infrared and opticalE chelleS pectrographs) will conduct a radial-velocity survey of ~ 300 M dwarfs with the 3.5m telescope at the Calar Alto Observatory. The CARMENES instrument is currently under construction; it consists of two independent échelle spectrographs, which together cover the wavelength range 0.55 – 1.7μm at a spectral resolution of R = 82, 000. The spectrographs and the fiber input are designed with a goal of 1m/s radial velocity precision using simultaneous calibration with emission-line lamps.